A Study on Effect of the Use of Various Leadership Style on Employee Motivation with Reference Through IT Company in Ahmedabad City - Dutta, Ananya; Chauhan, Sumit; Vidani, Jignesh (PT FORMOSA CENDEKIA GLOBAL, 2024)
The current study explores the impact of different leadership styles on employee motivation in an IT company in Ahmedabad. Based on a quantitative approach, results were extracted after analyzing the relationship between employee age and their perceptions of leadership decision-making, communication, and motivational strategies. The results indicate that participative leadership style has a high impact on employee motivation with the impact growing with the perception of whether employee opinions are sought. This provides recommendations for future work to be done on the impact of telecommuting, psychological safety, and motivation in an environment with demographic inequality. In this regard, the current study complements the findings on effective leadership practices that are productive in modern organizational settings by placing greater emphasis on practices that ensure higher employee motivation and productivity